Periglacial environments and frozen ground in the central Pyrenean high mountain area: Ground thermal regime and distribution of landforms and processes. (6th November 2019) - Serrano, Enrique; de Sanjosé‐Blasco, José Juan; Gómez‐Lende, Manuel; López‐Moreno, Juan Ignacio; Pisabarro, Alfonso; Martínez‐Fernández, Adrián
Abstract: The periglacial belt is located in the highest parts of temperate mountains. The balance between mean air and ground temperatures and the presence of water determine the effectiveness of periglacial processes related to permafrost, the active layer or seasonally frozen ground (SFG). This study combines thermal and geomorphological data obtained in four Pyrenean massifs (Infierno‐Argualas, Posets, Maladeta and Monte Perdido) to improve knowledge on the occurrence and distribution of frozen ground. The methodology used is based on the study of landforms as frozen ground indicators, mapping processes, ground temperature analysis, basal temperature of snow, thermal mapping and geomatic surveys on rock glaciers and protalus lobes. In the Pyrenean high mountain areas the lower limit of frozen ground is at 2, 650m a.s.l., possible permafrost appears above 2, 650m a.s.l. on north‐ and south‐facing slopes, and probable permafrost is dominant above 2, 900m a.s.l. Unfrozen ground with cold‐associated geomorphological processes reach 2, 900m a.s.l. and unfrozen and frozen ground distribution points to a patchy pattern throughout the periglacial belt. The most widespread frozen grounds are SFG. The thermal data, mean annual ground temperature, cold season temperatures, bottom temperature snow measurements, freeze/thaw cycles and distribution of landforms permit the establishment of a periglacial land system divided into three main belts: infraperiglacial, middle periglacial and supraperiglacial. The large number of processes and landforms that are involved and their altitudinal and spatial organization make up a complex environment that determines the geoecological dynamics of high mountain areas.